Three Golden Ages: Discovering the Creative Secrets of Renaissance Florence, Elizabethan England, and America's Founding - Mapp, Alf J. (Madison Books, 1998)
In this intriguing book, best-selling author Alf Mapp, Jr. explores three periods in Western history that exploded with creativity: Elizabethan England, Renaissance Florence, and America's founding. What enabled these societies to make staggering jumps in scientific knowledge, develop new political structures, or create timeless works of art?